Structure and mechanical properties of fiber-reinforced fly ash cement mortar - Yuliang Qi; Mengxiong Tang; Yuanbing Li; Zhe Qiao; Yichen Yu (Materials Research Express)
In this study, the modification of three types of fibers (basalt fiber, carbon fiber, high-silica fiber) on the structure and mechanical properties of cement mortar was investigated. Firstly, the basic mix proportion of the mortar was determined based on different contents of fly ash. The results revealed that the morphology effect of fly ash contributed to the improvement of mortar workability, reduction of water-binder ratio, and enhancement of mechanical properties of specimens. However, excessive fly ash led to severe carbonation in the cement mortar, damaging the structural compactness and adversely affecting the strength. The optimum content of fly ash was determined to be 4.45 wt%. Based on this, the optimal addition amounts of basalt fiber, carbon fiber, and high-silica fiber were determined to be 0.3 wt%, 0.6 wt%, and 0.3 wt% respectively. The main reinforcing mechanisms of each fiber in the mortar matrix were fiber fracture and fiber pull-out. Among them, the dispersion uniformity of basalt fiber was relatively poor, while the interface bond strength between carbon fiber and mortar matrix was optimal. The reinforced mortar incorporating carbon fiber exhibited a 28-day flexural strength, compressive strength, and elastic modulus of 18.0 MPa, 109.8 MPa, and 47.5 GPa respectively.